Study guide [for] A people and a nation. V.2 : since 1865 - Norton, Mary Beth.; .; Warre, George C.; Rickettson, Cynthia L. (Boston : Houghton Mifflin, 1998)
Reconstruction: a partial revolution, 1865-1877. The development of the West and South, 1865-1877. The machine age, 1877-1920. The Vitality and Turmoil of urban life, 1877-1920. Gilded age politics, 1877-1900...
Keywords: History; United States; Nation; United States -- Civilization